Japan's export specialization in 2000–2020 - Zoia S. Podoba (Elsevier, 2021)
By empirically examining the commodity structure of Japan's exports in 2000–2020, the authors have identified product groups with increased, diminished, newly emerged, and lost revealed comparative advantages (RCA). In 2020, Japan had RCA in 24 product groups with relatively high levels of product complexity and thus managed to maintain its highly diversified trade portfolio. However, increasing global competition poses potential risks to Japan's exports. Eight product groups with diminished and two product groups with lost RCA are signs of Japan's unsuccessful adaptation to the structural changes on the world markets. The newly emerged RCA, predominantly in the chemicals and allied industries, still mostly have lower index values in comparison to major trade partners, however, their contribution to Japan's exports is likely to expand. To enhance its comparative advantages, Japan should foster innovation which may positively affect national competitiveness but this depends on how the country will adapt to domestic and global challenges.